Effects of bariatric surgery on kidney diseases, cardiovascular diseases, mortality and severe hypoglycaemia among patients with Type 2 diabetes mellitus. Issue 8 (27th June 2020) - Wong, Carlos K H; Wu, Tingting; Wong, Simon K H; Law, Betty T T; Grieve, Eleanor; Ng, Enders K W; Wu, Olivia; Lam, Cindy L K
Abstract: Background: Bariatric surgery has been widely indicated for the management of obesity and related comorbidities. However, there are uncertainties pertaining to the risks of post-bariatric severe hypoglycaemia (SH), cardiovascular diseases (CVDs), end-stage kidney diseases (ESKDs) and all-cause mortality in obese patients with Type 2 diabetes mellitus (T2DM), especially among Asian populations. Methods: A retrospective population-based cohort of 1702 obese T2DM patients who were free of CVD and ESKD were assembled based on the 2006–17 Hospital Authority database. One-to-five propensity-score matching was used to balance baseline covariates between patients in bariatric surgery and control groups. Incidence rates (IRs) of SH, CVD, Stage 4/5 chronic kidney diseases (CKD), ESKD and all-cause mortality events for two groups were calculated. Hazard ratios (HR) for SH, CVD and Stage 4/5 CKD events were assessed using Cox-proportional hazard models. Changes in estimated glomerular filtration rate (eGFR) and urine albumin–creatinine ratio (UACR) were measured up to 60 months. Results: Over a mean follow-up period of 32 months with 5725 person-years, cumulative incidences of mortality, CVD, Stage 4/5 CKD, ESKD and SH were 0, 0.036, 0.050, 0.017 and 0.020, respectively. The surgery group had a significant reduction in risk of CVD events (HR = 0.464, P = 0.015) and no occurrence of mortality events. However, there were no significant differences in risks of SH [HR = 0.469, 95% confidence interval (CI): 0.204–1.081], Stage 4/5 CKD (HR =0.896, 95% CI: 0.519–1.545) and ESKD (HR = 0.666, 95% CI: 0.264–1.683) between two groups, although IRs were lower in the surgery group. Surgical patients had significantly higher eGFR within 12 months and had significantly lower UACR until 48 months. Conclusions: Among obese T2DM patients, bariatric surgery lowered the risk of CVD and mortality, and was beneficial towards the kidney outcomes.